Genome-Wide Survey Reveals the Microsatellite Characteristics and Phylogenetic Relationships of Harpadon nehereus - Tianyan Yang; Xinxin Huang; Zijun Ning; Tianxiang Gao (Current Issues in Molecular Biology, 2021)
Harpadon nehereus forms one of the most important commercial fisheries along the Bay of Bengal and the southeast coast of China. In this study, the genome-wide survey dataset first produced using next-generation sequencing (NGS) was used to provide general information on the genome size, heterozygosity and repeat sequence ratio of H. nehereus. About 68.74 GB of high-quality sequence data were obtained in total and the genome size was estimated to be 1315 Mb with the 17-mer frequency distribution. The sequence repeat ratio and heterozygosity were calculated to be 52.49% and 0.67%, respectively. A total of 1,027,651 microsatellite motifs were identified and dinucleotide repeat was the most dominant simple sequence repeat (SSR) motif with a frequency of 54.35%. As a by-product of whole genome sequencing, the mitochondrial genome is a powerful tool to investigate the evolutionary relationships between H. nehereus and its relatives. The maximum likelihood (ML) phylogenetic tree was constructed according to the concatenated matrix of amino acids translated from the 13 protein-coding genes (PCGs). Monophyly of two species of the genus Harpadon was revealed in the present study and they formed a monophyletic clade with Saurida with a high bootstrap value of 100%. The results would help to push back the frontiers of genomics and open the doors of molecular diversity as well as conservation genetics studies on this species.